(untitled) - Hinkle, Deborah (New York, 2005)
McGraw-Hill Technology Education’s Professional Approach Series presents exercises in real-life business situations so students get hands-on experience working on actual projects--the best way to prepare them for the on-the-job challenges they'll face. Each lesson contains up to 25 skill-applications and 5 end-of-unit skill-applications that take students from simple to complex situations. The Office 2003 texts complete instruction in all skill sets and activities for the appropriate Microsoft Office Specialist Certification (MOS) Exams.
Keywords: Office automation,Word processing,Word ( computer programs )